Socio economic characteristics and its effect to tea farming management behavior of tea smallholders in West Java Province - Sita, Kralawi (Research Institute for Tea and Cinchona, 2015)
The research aimed to: 1) described the socio-economic characteristics of tea small-holders in West Java Province; 2) described tea farming management behavior of tea small-holder in West Java Province; and 3) analyzed the effect of socio-economic characteristics to a behavior of tea farming management. The research took place in nine tea smallholder plantation center in West Java Province where the Program of National Tea Agribusiness Improvement Action held. The research method used descriptive study with quantitative app-roach. The sampling method used proportional random sampling with 320 respondents or at least 5% from population area. Data analyzed used multiple linear regression analysis with Backward Model through SPPS 21.0 program. The result showed that tea smallholders have a certain socio-economic characteristics in mana-ging their tea farming. Behavior tea small-holders in tea farming management showed similarities and differences. The limited access to productive resources, technology, informa-tion, market, financial and extension make management on tea farming not optimal. Eco-nomic variables i.e. gender, main job, tea pro-ductivity, tea prices, and tea farming income positively significant to tea farming mana-gement behavior of tea smallholders. Its va-riables have the power to encourage and to motivate potential influence and spirit of tea smallholders in managing their tea farming.